A prelude of a 'little army'? São Paulo police force in the early years of the Republic (1890-1895) - Rosemberg, Andre [UNESP] (Univ do Vale do Rio Dos Sinos, 2012)
This article analyzes the creation and development of the São Paulo police force during the early years of the republican regime. In a period of political change and turbulence, institutional upheaval (uprising of the Navy and federalist revolution), and social pressure, São Paulo's police force played an important role. As the state sought to organize the public sphere, the police force became a tool in the new government's hands. A more martial set of demands mobilized a large portion of the troops on behalf of the federal government against the Custodio de Mello uprising, and sought to defend São Paulo's borders. Despite official discourse that fomented a militarized response, São Paulo's police force found itself unable to dismiss old personnel and practices and dislodge entrenched interests.
Keywords: police; Revolta da Armada; Revolucao Federalista; São Paulo; Republic